The Firm as a Coordination System: Evidence from Software Services Offshoring - Srikanth, Kannan; Puranam, Phanish (Organization Science, 2014)
To examine what, if any, are the differences in how activities are coordinated within versus between firms, we conducted interviews with 32 project managers regarding 60 projects in the offshore software services industry. Uniquely, our projects were sampled along two dimensions: (1) colocation versus spatial distribution and (2) delivery by groups of individuals from a single firm versus from multiple firms. Our evidence suggests that in colocated projects, the same broad categories of coordination mechanisms are used both within and between firms. However, there is a qualitative difference in how geographically (i.e., spatially) distributed projects are coordinated within versus between firms. Distributed projects conducted within firms rely extensively on tacit coordination mechanisms; such mechanisms are not readily available in between-firm projects that are spatially distributed. This difference may arise because of the lack of shared history and lack of enforcement through common authority in the between-firm context.